2016
DOI: 10.1111/ncn3.12092
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic alignment in standing, and its relationship with trunk control and motor recovery of lower limb after stroke

Abstract: Background: The pelvis is not stable after stroke, and poor trunk recovery might be the foremost contributor to altered pelvic alignment in sitting, standing and during walking. Aim: To analyze the relationship between pelvic alignment in standing and trunk control after stroke, and also test how these correlations are related to Brunnstrom's lower limb motor recovery. Methods: In the present cross-sectional study, 116 ambulant patients after stroke were assessed for their pelvic tilt angles in standing and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 25 publications
2
25
0
Order By: Relevance
“…These test positions were standardized and are showed in Appendix 2. The angle of lateral and anterior pelvic tilt in standing was measured using the palpation meter, a reliable device to measure pelvic instability in stroke [5, 7, 20]. The gait speed and cadence were calculated after a 10-m walk test [21].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These test positions were standardized and are showed in Appendix 2. The angle of lateral and anterior pelvic tilt in standing was measured using the palpation meter, a reliable device to measure pelvic instability in stroke [5, 7, 20]. The gait speed and cadence were calculated after a 10-m walk test [21].…”
Section: Methodsmentioning
confidence: 99%
“…In a recent cross-sectional study, it was observed that poor trunk control and lower extremity recovery are related to the pelvis instability in patients with chronic stroke [5]. Altered pelvic alignment in the standing position resulting from poor lower trunk control after stroke shall positively influence the balance, gait and functional performance [6].…”
Section: Introductionmentioning
confidence: 99%
“…Tanaka and colleagues [28] stated that weakness of trunk muscles in hemiplegic patients resulted from the upper motor neuron lesion and disuse. In Anatomically, a part from the rectus abdominal muscle and the rest of the abdominal muscles are attached to the linea alba through central aponeurosis fascial expansions bilaterally [9]. During initiation of STS movement, the results of the present study showed a significant decrease of anterior pelvic tilt angle of both stroke groups compared with control.…”
Section: Discussionmentioning
confidence: 46%
“…Pelvic movements are also integrated in all functional activities [8]. After stroke, the patient's pelvis becomes unstable [9].…”
Section: Introductionmentioning
confidence: 99%
“…This was supported by the recent work in which the lateral tilt toward the most affected side and anterior pelvic tilt in standing were moderately correlated to trunk control, and these correlations were high in chronic stroke patients with better lower limb motor recovery. [15]…”
Section: Discussionmentioning
confidence: 99%